Effect of Dynamic Position Changes on Adenoma Detection During Colonoscope Withdrawal: A Randomized Controlled Multicenter Trial. (January 2016) - Lee, Seung‐Woo; Chang, Jae Hyuck; Ji, Jeong‐Seon; Maeong, Il Ho; Cheung, Dae Young; Kim, Joon Sung; Cho, Young‐Seok; Chung, Wook‐Jin; Lee, Bo‐In; Kim, Sang‐Woo; Kim, Byung‐Wook; Choi, Hwang; et al.
Abstract : OBJECTIVES: Adequate luminal distension is essential for improving adenoma detection during colonoscope withdrawal. A few crossover studies have reported that dynamic position changes maximize luminal distension and increase adenoma detection rates (ADR). We designed a multicenter, randomized, parallel‐group trial to verify the effect of dynamic position changes on colonic adenoma detection. METHODS: This study was conducted at the six hospitals of the Catholic University of Korea. Patients aged 45–80 years who underwent a colonoscopy for the first time were included. In the position change group, the position changes during colonoscope withdrawal were as follows: cecum, ascending colon, and hepatic flexure: left lateral position; transverse colon: supine position; splenic flexure, descending colon, sigmoid colon, and rectum: right lateral position. In the control group, the examinations were performed entirely in the left lateral position during colonoscope withdrawal. The primary outcome measure was the ADR, which was defined as the proportion of patients with ≥1 adenoma. RESULTS: A total of 1, 072 patients were randomized into the position change group (536 patients) or the control group (536 patients). The ADR was higher in the position change group than in the control group (42.4 vs. 33.0%, P =0.002). More adenomas were detected per subject in the position change group (0.90 vs. 0.67, P =0.01). Increases in the number of adenomas were observed in examinations of the transverse colon (0.22 vs. 0.13, P =0.016) and the left colon (0.37 vs. 0.27, P= 0.045). A significant increase in the ADR was observed for endoscopists with a relatively low detection rate. For endoscopists with a high detection rate, non‐significant changes in the ADR were observed. CONCLUSIONS: Dynamic position changes during colonoscope withdrawal increased the ADR.